HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PARTISIPASI PEDAGANG DALAM PENGELOLAAN SAMPAH DI PASAR LABEAN KECAMATAN BALAESANG KABUPATEN DONGGALA - Matius Paundanan; Sutriani (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2023)
Waste management in Indonesia is still a problem that cannot be handled as well as in the Labean Market. The purpose of this study was to determine the relationship between knowledge and attitudes with the participation of traders in waste management at the Labean Market, Balaesang District, Donggala Regency, Central Sulawesi. This type of research is analytic with a cross sectional approach. Data collection using a questionnaire. Data analysis used univariate and bivariate analysis with the Chi-Square test. The sample in this study amounted to 32 people. The results showed that there was a relationship between knowledge and trader participation, with a p-value = 0.013 (p-value ≤ 0.05), trader attitudes and trader participation, with a p-value = 0.046 (p-value ≤ 0, 05). The conclusion in this study is that there is a significant relationship between knowledge and attitudes with the participation of traders in waste management at the Labean Market, Balaesang District, Donggala Regency, Central Sulawesi.